Students’ Perceptions on Online Clinical Learning amid the COVID-19 Pandemic in an Institution of Higher Learning: A Qualitative Inquiry - Jean Mukasa; Doreen Macherera Mukona; Smitha Joseph; Anupama Kanissery; Joemol James; Maribeth Carpio Tabay; Salimbabu Abdulla; Hussam Al Amoor (The Scientific World Journal)
Institutions of learning have been disrupted globally with serious implications for clinical teaching for students of health professions. The purpose of our study was to explore the perceptions of students towards online clinical teaching during the COVID-19 pandemic at Fatima College of Health Sciences. This was a descriptive qualitative study conducted on a purposive sample of 25 students from 24 June to 30 August 2020. The sample size was determined by data saturation. These were mainly nursing students in their 2nd to the 4th years of study. Students are required to have experiences, of stipulated nature and duration, in various specialty clinical settings throughout the clinical years of their programs. Approval for the study was granted by the Fatima College Research Ethics Committee (approval number: INTSTF010BSN20). The research was conducted according to the requirements of the Declaration of Helsinki. Data were collected through online semistructured questionnaires. Prospective participants were sent a soft copy of the informed consent document, and consent was indicated by clicking an “agree” link on the page that took them to the questionnaire. All participants were informed of their freedom to either participate in the study or not, without any penalty and were assured of their confidentiality. The questionnaires were kept in a password-protected file to which the researchers had sole access. Manual thematic analysis was done following the stages of organisation, familiarisation, transcription, coding, developing a thematic framework, indexing, displaying, and reporting. The major themes identified were the unfamiliar experience, challenges of online clinical learning, and possible solutions. Challenges of online clinical learning are multifaceted and require concerted multidisciplinary efforts to resolve. Nursing institutions, ours included, must develop flexible education systems that will be able to thrive in crisis and other unforeseeable circumstances.